Impact of online instructor scaffolding strategies on students' speaking performance / Sandra Phek-Lin Sim, Hannah Phek-Khiok Sim and Cheng-Sim Quah - Sim, Sandra Phek-Lin; Sim, Hannah Phek-Khiok; Quah, Cheng-Sim (Universiti Teknologi MARA, Perak, 2023)
Students need to master oral communication skills during their university studies to prepare them for future working environment. However, many ESL students are facing difficulties communicating in English because they seldom use English for interaction outside their English classes. Additionally, they lack proper guidance from instructors on how to improve their speaking skills. Thus, this study aims to identify the types, usefulness, and impact of Online Instructor Scaffolding Strategies on students' speaking performance. A mixed-method research design was utilised in this study. The instruments used in data collection included an open-ended questionnaire designed by the researchers, pre-test and post-test, recorded videos of students' role-play, and instructor's online feedback. The participants were 66 mixed-proficiency level students from a university in Malaysia. The findings revealed various useful online instructor scaffolding strategies enhanced students' speaking performance. Post-test results showed that the Online Instructor Scaffolding Strategies have an impact on students' speaking performance. The findings from this study are meaningful as Online Instructor Scaffolding Strategies can benefit students of all proficiency levels to improve their speaking performance.